2001
DOI: 10.3171/foc.2001.11.3.3
|View full text |Cite
|
Sign up to set email alerts
|

Motor cortex stimulation for neuropathic pain

Abstract: Motor cortex stimulation is increasingly reported in the literature as a surgical option for the alleviation of neuropathic pain. The authors review the published literature and present their results including those demonstrated in a randomized controlled trial that confirmed the efficacy of the procedure. Patient selection and prediction of outcomes, however, remain difficult issues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 22 publications
1
43
0
Order By: Relevance
“…The 46.1% of the patients with more than 50% pain relief and the 69.2% with more than 40% pain relief observed in this study are similar to the rates obtained in other studies 1,14,15 , which observed that 50% of the patients treated with MSC had over 50% pain relief. In a critical review of the literature, Fontaine et al noticed that a good response to MCS (pain relief ≥40-50%) was observed in around 55% of the patients who underwent surgery, and in 45% of the 152 patients with a postoperative follow-up ≥1 year 16 .…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…The 46.1% of the patients with more than 50% pain relief and the 69.2% with more than 40% pain relief observed in this study are similar to the rates obtained in other studies 1,14,15 , which observed that 50% of the patients treated with MSC had over 50% pain relief. In a critical review of the literature, Fontaine et al noticed that a good response to MCS (pain relief ≥40-50%) was observed in around 55% of the patients who underwent surgery, and in 45% of the 152 patients with a postoperative follow-up ≥1 year 16 .…”
Section: Discussionsupporting
confidence: 80%
“…The motor response in the painful area may also be useful. However, as pointed out by Smith et al 1 , the results from such tests are not a guarantee of a successful outcome. Therefore, we did not routinely perform any prediction-specific assessments.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations